Pengaruh Profitabilitas, Solvabilitas, Dan Pertumbuhan Penjualan Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Siregar, Astri Fadhila; Azhar, M. Karya Satya; Arief, Muhammad (Cattleya Darmaya Fortuna, 2024)
This research aims to determine profitability, solvency, and sales growth on profit growth with firm size as a moderating variable in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2019 - 2023. The sample selection method used is purposive sampling. The total observations in this study were 100 observations consisting of 20 companies. The data analysis technique used in this study is moderation analysis using the interaction test with the SPSS version 26. The test results of this research indicate that simultaneously profitability, solvency, sales growth, and firm size affect profit growth. Partially, solvency and sales growth affect profit growth, while profitability has no effect on profit growth. Firm size is able to moderate and strengthen the effect of profitability and sales growth on profit growth, but is unable to moderate the effect of solvency on profit growth.